VBL Learning Device Validation (Tracker) on GJB Material Through the PBL Model - Pratama, Bagus; Diyana, Tsania Nur (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2023)
This study aims to describe the validity of the VBL learning device (Tracker) on GJB material through the PBL model. This research is research and development, but this article is only at the validity stage. The research instrument used is a validation sheet. The resulting learning tools are validated by one expert. The results of the analysis show that 1) the validity of the device in terms of the validation of the RPP (Learning Implementation Plan) obtains a score of 3.65 in the valid category, the validity of the LKPD (Student Worksheets) obtains a score of 3.81 in the valid category, and the validity of the THB (Learning Outcomes Test) obtains score 4 valid theory. It was concluded that the VBL learning tool (Tracker) on GJB material through the PBL model is in the valid category so that it can be used for the next development stage.